Impact of Digital Streamers’ Language on the Moral Development of Vietnamese Adolescents: A Qualitative Inquiry - Le, Thanh Thao; Pham, Trut Thuy (Universitas Veteran Bangun Nusantara, 2024)
This qualitative study investigates the impact of streamers’ swearing on the morality of Vietnamese teenagers, a topic of increasing importance in the era of digital streaming and online entertainment. The research was conducted through semi-structured interviews with nine Vietnamese teenagers, providing in-depth insights into their perceptions and attitudes towards the language used by streamers and its influence on their behavior. The thematic analysis of the interview data revealed four key themes: normalization of swearing in digital spaces, delineation between online and offline behaviors, influence of streamers as role models, and critical reflection and selective adoption. The study found that while swearing by streamers was normalized in digital contexts, participants also demonstrated a clear distinction between acceptable behaviors in online and offline environments. Streamers were often viewed as influential role models, affecting the language and attitudes of the adolescents. However, participants also engaged in critical reflection, selectively adopting behaviors that aligned with their personal and cultural values. These findings contribute to the understanding of digital media’s impact on adolescent development, particularly in non-Western contexts. The study underscores the complex interplay between cultural norms, digital media consumption, and moral development, highlighting the need for comprehensive digital literacy and ethical content creation in the digital age.